Pemanfaatan Instagram dan TikTok sebagai Media Komunikasi Digital dalam Pembelajaran Bahasa Indonesia Bagi Penutur Asing (BIPA): Sebuah Kajian Pustaka dan Analisis Isi - Renny Soelistiyowati; Harries Marithasari; Alfa Taufan Latif; Rici Tri Harpin Pranata; Fahmi Fuad Cholagi (Jurnal Penelitian Sosial Ilmu Komunikasi, 2026)
The development of social media opens up new opportunities in language learning, including Indonesian for Foreign Speakers (BIPA). Instagram and TikTok have the potential to become complementary learning media that are multimodal, flexible, and interactive. This study aims to analyze the use of the two platforms in supporting the development of listening, reading, speaking, and writing skills of BIPA learners. The research uses a qualitative approach with literature study methods and content analysis techniques. The data in the form of 15 scientific articles were selected objectively based on the criteria of relevance to technology-based language learning and BIPA, published in the 2021–2025 range, and came from SINTA, Scopus, and other trusted academic journals. Data was collected through Google Scholar, Scopus, and SINTA searches. The analysis was carried out through the stages of data reduction, categorization, synthesis, and drawing conclusions to identify patterns of social media use in BIPA learning. The results show that Instagram is effectively used to present Indonesian vocabulary, grammar, and culture through structured visual content, while TikTok supports the development of productive skills through content creation, short videos, and digital collaboration. Both platforms have been shown to increase learning motivation, learner engagement, and exposure to the use of authentic language. However, its use requires systematic pedagogical planning to be in harmony with learning achievements. This study concludes that Instagram and TikTok have great potential as complementary media for BIPA learning when combined with the right pedagogical strategy.